Food Security and Poverty Depth in Indonesia: Evidence from Provincial Fixed-Effects Panel Data (2019–2023) - Fathimah Kurniawati (Institut Agama Islam Sunan Giri Ponorogo, 2026)
This study examines the relationship between food security and poverty depth in Indonesia using provincial panel data from 34 provinces during 2019–2023. Poverty depth is measured using the Poverty Gap Index, while food security is represented by the Food Security Index. Using a fixed effect panel model with cluster robust standard errors, this study finds that food security has a negative but statistically insignificant effect on poverty depth. In contrast, GRDP per capita, unemployment, and social assistance expenditure significantly affect poverty depth. These findings suggest that poverty depth in Indonesia is more strongly associated with labor market conditions, the inclusiveness of economic growth, and social protection responses than with short-term changes in aggregate food security. This study contributes to the literature by shifting the focus from poverty rate to poverty depth and by examining food security as a determinant of the poverty gap at the provincial level. The findings imply that food security policies should be integrated with employment creation, inclusive growth strategies, and regionally adjusted social assistance to reduce poverty depth more effectively.